FELLESSKAPETS SAMMENBRUDD OG KOLLEKTIV SMERTE - Henriksen, Georg (Tidsskriftet Antropologi, 1996)
Georg Henriksen: The collapse of the community and collective pain This article deals with the the collapse of a community and the pain felt by the individuals living in it. It understands pain as an experience which is at the same time collective and individual, shared and existential. Since 1996 Georg Henriksen has foliowed the Mushuau Innu, an Indian community in the northem part of Canada. With informant’s experience from this community as reference Henriksen points out how the levels of individual, community, and over all social, eco- nomical, and political processes are interwowen. By being integrated in white society the Innu have lost their own social and moral order and at the same time they have stayed marginalized in relation to the surrounding society. The result of this intemal collapse and extemal marginalization is anomie - suicides, drinking, violence and the feeling of loneliness. Henriksen points out the responsibility of the govemment to establish a political and social field for the Innu to exist in and the necessity of understanding and bringing an end to the structural violence inflicted on the Innu.